Literature Study: Relationship between Inquiry Model and Ability to Understand Mathematical Concept and Students' Learning Independence - Ulya, Syastri; Mulyono, Mulyono; Neem, Chuti (International Journal of Multidisciplinary Research of Higher Education, 2024)
The application of the inquiry learning model is often related to students' ability to understand mathematical concepts and self regulated in mathematical learning. This is one of the reasons why the relationship between the inquiry learning model and the ability to understand mathematical concepts and self regulated in mathematical learning is interesting to discuss again. Studies regarding the relationship between the inquiry learning model and the ability to understand mathematical concepts and independent mathematical learning have been carried out since the 1960s until now. With the large amount of literature regarding the inquiry learning model on the ability to understand concepts and self regulated in mathematical learning, this article aims to map existing studies on the relationship between the inquiry learning model and the ability to understand concepts and self regulated in mathematical learning. This article is a study that uses a literature study approach. Literature such as books, articles and journals were collected online, namely with the help of the "publish or perish 8" tool using the Google Scholar category as a search in 2018 to 2023 using two keywords, namely "Inquiry Learning Model on the Ability to Understand Mathematical Concepts" and "Learning Model Inquiry into Mathematical learning self regulated”, then connected with Mendeley 1.19.8 as the reference management found. This study found that there is a relationship between the inquiry learning model and students' mathematical problem solving abilities and students' Mathematical learning self regulated. There are 31 articles discussing the inquiry learning model on mathematical problem solving abilities and 27 articles discussing the inquiry learning model on learning independence. In the end, this study came to the conclusion that there is a relationship between the inquiry learning model and the ability to understand concepts and independent mathematical learning.